A Study on Deixis in “Our Song” Lyrics by Anne Marie - Basuki, Vaviolla Aisyah; Husnussalam, Hendra (PROJECT (Professional Journal of English Education), 2025)
The objective of the study is to analyze the type and/or dominance of deixis; further, to identify deixis in a song’s lyrics entitled “Our Song” composed by Anne Marie. This analysis method, in fact, is to discover features of deixis emerging in the song’s lyrics. In practice, the study performed descriptive qualitative method to project data from deixis model appears in the lyrics. The findings reported, in personal deixis, eighty (80) deictical words distinguished the first person, the second person, and the third person, by pronoun (I, me, my, our, and we), possessive pronouns (you), and pronoun (it), respectively. For spatial deixis and temporal deixis, twenty-nine (29) deictical words were identified in the song’s lyrics of “Our Song” by Anne Marie. The dominant deictical words on spatial deixis of the song’s lyrics were on the radio. The dominant deictical word for temporal deixis of the song’s lyrics was when. 73% of the deictical words discovered in the song’s lyrics was written in personal deixis; thus, indicated that the dominant deictical word was personal deixis.